Location Decisions and Nongovernmental Organization Motivation : Evidence from Rural Bangladesh - Gauri, Varun; Fruttero, Anna (World Bank, Washington, DC, 2014)
Nongovernmental organizations (NGOs) play an increasingly important role in development assistance, but little systematic evidence is available about their objectives and choices in developing countries. The authors develop two stylized accounts of NGO motivation: one in which donor contracts determine location decisions, and another in which altruistic motivations are the principal determinants. The authors then use data from the 1995 and 2000 rounds of the Bangladesh Households and Income and Expenditure Survey to analyze location decisions of NGO programs established between those two sample years. The data show that net change in a community's NGO program was unrelated to the community's need and that NGOs were ready to establish new programs in new areas without being concerned of duplicating the efforts of other NGOs. The findings suggest that contracts with donors, implicit or explicit, probably play a crucial role in determining the incentives that affect NGO program location choices.